Communication privacy management in Social Network Sites: the influence of parental involvement and social on information disclosure - Syed Hassan , Sharifah Sariah; Hashim, Che Noraini (Scottish Group of Education and Testing Services, 2014)
The trend of research in Social Network Sites have focused on privacy disclosure and its effect on motivation and security . Nevertheless, privacy disclosure needs further attention to address adolescence well being and positive behavior. This study seeks to investigate factors related to parental involvement and social influence on privacy disclosure that influence adolescences' well being. Underpinning the framework of Petronio‘s theory of Privacy Management,the study extended the factors of culture, social and motivation to explain the behavior of privacy disclosure. Using Structural Equation modeling analysis, this study estimated the relationships of privacy management influential factors and well being. The implications of the study included the intervention of parents, schools and universities to educate students formally and informally.